2017
DOI: 10.3390/atmos8120247
|View full text |Cite
|
Sign up to set email alerts
|

Urban Roughness Estimation Based on Digital Building Models for Urban Wind and Thermal Condition Estimation—Application of the SkyHelios Model

Abstract: Roughness length is a critical parameter for estimation of wind conditions, and it is therefore also relevant for the estimation of human thermal conditions in urban areas. The high density of buildings in urban areas causes large changes in land coverage, thereby increasing surface roughness. This influence atmospheric flow and also leads to a reduction in urban air ventilation, thus increasing the risk of human thermal stress. In this study, a digital building model of Tainan city was used to calculate rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Referring to the earlier study of Lin, et al [71], the calculation of SVF was based on a classic single-point SVF (or SVF SP ) within a fixed point, so as to obtain a “fisheye view”, with a calibrated height of 1.1m (which is complacent with the gravity centre of the human body as described by Kuttler [63]). As shown in Figure 1, each fixed point (henceforth reference point (RP)) within the UCCs was tested within the SkyHelios model (Research Center Human Biometeorology; Freiburg, Germany; ) [72,73], to identify the SVF SP at each RP. Such a methodology was already utilized by numerous other studies ([23,54,69] for symmetrical canyons, and [55,74] for asymmetrical canyons).…”
Section: Methodsmentioning
confidence: 99%
“…Referring to the earlier study of Lin, et al [71], the calculation of SVF was based on a classic single-point SVF (or SVF SP ) within a fixed point, so as to obtain a “fisheye view”, with a calibrated height of 1.1m (which is complacent with the gravity centre of the human body as described by Kuttler [63]). As shown in Figure 1, each fixed point (henceforth reference point (RP)) within the UCCs was tested within the SkyHelios model (Research Center Human Biometeorology; Freiburg, Germany; ) [72,73], to identify the SVF SP at each RP. Such a methodology was already utilized by numerous other studies ([23,54,69] for symmetrical canyons, and [55,74] for asymmetrical canyons).…”
Section: Methodsmentioning
confidence: 99%
“…For an array of the equivalent height of roughness element, an excess of λ P can lead to the excess of the displacement height and a reduction of the roughness of the obstacle array as λ P , tends to 1. This means that the elements are so close that they merge to form a new surface (Chen, Fröhlich, Matzarakis & Lin, 2017). The ratio of displacement height over the roughness element height is given as:…”
Section: Processingmentioning
confidence: 99%
“…At  =0.1, this means the elements are so close and they merge to form a new surface (9). For this method, the most important benefits are that the values of the length of roughness which can be calculated without the need for high towers, as well as their means.…”
Section: Figure 1: Dimensions How To Calculate (A P a T )mentioning
confidence: 99%
“…Roughness lengths were also evaluated for Kalpakkam site, India, using terrain features by Jesan et al They observed maximum and minimum roughness lengths of 0.48 m to 0.26 m, respectively (8). Finally, Chen et al calculated roughness length using an approach based on digital building model of Tainan city using an approach based on Voronoi cells by applying the microclimate (9).…”
mentioning
confidence: 99%